Perebutan Panggadereng di Kerajaan LOkal di Jazirah Sulawesi Selatan Abad XV-XVII - Bahri Bahri (Universitas Negeri Yogyakarta, 2016)
This study aims to determine the history of the struggle for Panggadereng in United Local, South Sulawesi XV-XVII century. The method that the researchers used in the writing of this history is a research method according Kuntowijoyo. The stages of historical research by Kuntowijoyo has five stages, the selection of topics, heuristics, verification, interpretation, and writing.Gowa and Bone kingdom are two forces that are very influential in the political constellation in Jasirah South Sulawesi in the kingdom. The power struggle between the two kingdoms not only occur during the reign of Sultan Hasanuddin in Gowa and reign in the kingdom Palakka White Bone, but long before the two kingdoms have been involved in the struggle pangadereng in the region. This lasted until after the treaty of bongaja which has also been involved in a contradiction that VOCs. Keywords: Power struggle, Local Kingdom, South Sulawesi.